The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12663-020-01449-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Telemedicine for Facio-Odontogenic Pain Management During COVID-19 Pandemic

Abstract: Introduction As the COVID-19 pandemic is increasingly griping the world, the entire landscape of existing patient management needs to be changed to avoid spread of Corona virus. In cases of emergencies, there is no option other than getting in-person consultations with doctors. But, in non-emergency patients, telemedicine can serve as a boon. Material and methods In this article, we have tried to summarize the rules, regulations and protocols in accordance with government guidelines along with practical manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“… 23 In addition, it has been reported that the use of telemedicine is beneficial for the management of orofacial pain during the COVID-19 pandemic. 24 Teledentistry, which was popular prior to the COVID-19 pandemic, has advantages such as allowing patients to meet with a specialist dentist without travelling a long distance, lowering costs and reducing the need for patients to take time off from work, but it has limitations such as screening, consultation and history taking, lack of experience in healthcare providers with the software and technology used, and the necessity for patients to have a dialogue with different people every time due to the virtual environment are described as the weaknesses. 25 Teledentistry, within the subcontexts of teleconsultation, teletriage, telediagnosis and telemonitoring, has been reported as potential solutions for current dental practices during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In addition, it has been reported that the use of telemedicine is beneficial for the management of orofacial pain during the COVID-19 pandemic. 24 Teledentistry, which was popular prior to the COVID-19 pandemic, has advantages such as allowing patients to meet with a specialist dentist without travelling a long distance, lowering costs and reducing the need for patients to take time off from work, but it has limitations such as screening, consultation and history taking, lack of experience in healthcare providers with the software and technology used, and the necessity for patients to have a dialogue with different people every time due to the virtual environment are described as the weaknesses. 25 Teledentistry, within the subcontexts of teleconsultation, teletriage, telediagnosis and telemonitoring, has been reported as potential solutions for current dental practices during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they rely on self‐reported information gathered through online resources 16,17 . With the advent of the internet, managing bruxism has taken on a new dimension 18–21 . People are now more aware of health‐related issues and can purchase over‐the‐counter appliances online to manage their bruxism, snoring, and sleep apnea 22 without consulting a dentist or medical professional 16 …”
Section: Introductionmentioning
confidence: 99%
“…16,17 With the advent of the internet, managing bruxism has taken on a new dimension. [18][19][20][21] People are now more aware of health-related issues and can purchase over-the-counter appliances online to manage their bruxism, snoring, and sleep apnea 22 without consulting a dentist or medical professional. 16 However, the quality of the information available online may not always be reliable.…”
mentioning
confidence: 99%
“…Following the onset of the COVID‐19 pandemic in 2020, hospitals and dental clinics temporarily limited their patient services and instead relied upon telemedicine to provide consultations and follow‐up visits remotely. Various medical and dental specialties, including oral and maxillofacial surgery and oral medicine, have since adapted by providing care remotely and continue to do so 1–3 . However, the use of telemedicine in orofacial pain for examination, evaluation, and diagnostic utility has not been well described.…”
Section: Introductionmentioning
confidence: 99%